Molecular identification by polymerase chain reaction-restriction fragment length polymorphism of commercially important lithodid species (Crustacea: Anomura) from southern South America - Pérez Barros, Patricia (2020)
King crab fisheries constitute a highly profitable marine business in southern South America, where five fisheries for lithodids currently exist, two in Chile and three in Argentina. These fisheries mainly target Lithodes santolla, however in some localities the harvested morphospecies is Lithodes confundens, and in some others it constitutes a mixed fishery since it also captures Paralomis granulosa. Fishery products can be commercialized as frozen shredded or canned minced meat, making specific identification unfeasible since the morphological characters used in the identification are on the carapace, and consequently, not available in these processed products. Therefore, a potential for food fraud exists, since southern king crab meat (L. santolla/ L. confundens) could be replaced by the less expensive false southern king crab, i.e. P. granulosa. Furthermore, incongruence between morphological and genetic characters rendered the taxonomic status of both morphospecies of commercial Lithodes questionable, and stressed the need of implementing molecular methods to monitor the abundance and distribution, as well as the landings, of each genetic clade of L. santolla/ L. confundens. In the present study, we developed rapid and cost-efficient Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) tests that can aid in the identification of commercially important lithodids that inhabit waters off southern South America in cases where identification is not possible using morphological characters.